2011
DOI: 10.3109/09513590.2010.495431
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective case–control study comparing hysteroscopic resection versus hormonal modulation in treating menstrual disorders due to isthmocele

Abstract: In a retrospective case-control study, we compared the effectiveness of hysteroscopic correction and hormonal treatment to improve symptoms [postmestrual abnormal uterine bleeding (PAUB), pelvic pain localized in suprapubic site] associated with isthmocele. Women (n = 39; mean age ± SD, 35 ± 4.1 years) were subdivided in Group A [patients (n = 19) subjected to hysteroscopic surgery (isthmoplasty)] and, Group B [women (n = 20) undergoing hormonal treatment consisting of one oral tablet containing 0.075  mg of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 15 publications
1
61
0
4
Order By: Relevance
“…Whatever the source of the blood in the isthmocele may be, its presence may contribute not only to PAUB but also to secondary infertility by negatively affecting mucus and sperm quality and interfering with embryo implantation [8]. The prevalence of symptomatic or clinically relevant CSDs reported in the literature ranges from 19.4% to 84% [9]. Possible risk factors for CSD include the number of cesarean sections, uterine position, labor before cesarean section, and the surgical technique used to close the uterine incision.…”
Section: Discussionmentioning
confidence: 97%
“…Whatever the source of the blood in the isthmocele may be, its presence may contribute not only to PAUB but also to secondary infertility by negatively affecting mucus and sperm quality and interfering with embryo implantation [8]. The prevalence of symptomatic or clinically relevant CSDs reported in the literature ranges from 19.4% to 84% [9]. Possible risk factors for CSD include the number of cesarean sections, uterine position, labor before cesarean section, and the surgical technique used to close the uterine incision.…”
Section: Discussionmentioning
confidence: 97%
“…Before offering a large surgical procedure with possible complications to women with spotting or dysmenorrhoea, we have the opinion that hormones should be offered first, although there is limited evidence on the effectiveness of hormonal therapy on niche‐related symptoms 36, 37. Future studies are needed to evaluate the effectiveness of hormonal therapies in comparison to hysteroscopic or laparoscopic niche resection, dependent on the size of the niche, the RM and future desire to conceive.…”
Section: Discussionmentioning
confidence: 99%
“…A hysteroscopic niche resection is the least invasive of these techniques, but requires a sufficient thick residual myometrium between the niche and the bladder to prevent bladder injury 13. A hysteroscopic niche resection can be performed in different ways: the lower rim (closest to the external cervical os) can be resected to facilitate menstrual outflow (Figure1);14, 15, 16, 17 both the lower and the upper part of the niche can be resected;18, 19, 20, 21 and this can be combined with coagulation of the vessels in the niche,16, 18, 19, 20, 21 or the entire niche surface 14, 15. Previous cohort studies reported a reduction of postmenstrual spotting in 80–90% of women, and a reduction in pain in 97% of women, in the absence of complications 13, 22, 23.…”
Section: Introductionmentioning
confidence: 99%
“…The mean reduction in the number of days of spotting compared with baseline was reported in two studies, and varied between 2 and 4 days in 119 women. 15,17 Apart from the flawed comparability and lack of randomisation, the studies did not use validated tools to measure the outcomes 13, 14, 15, 16, 17, 18, 19, 20, 21. We initiated a randomised controlled trial assessing the effect on postmenstrual spotting of a hysteroscopic niche resection versus no treatment.…”
Section: Introductionmentioning
confidence: 99%